The Active Compounds and Therapeutic Target of Tripterygium wilfordii Hook. f. in Attenuating Proteinuria in Diabetic Nephropathy: A Review - Liu, Peng; Zhang, Jing; Wang, Yun; Shen, Zhengri; Wang, Chen; Chen, Dan-Qian; Qiu, Xinping (Frontiers in Medicine, 2021)
Tripterygium wilfordii Hook. f. (TWHF) is a traditional Chinese herbal medicine and widely used to treat diabetic kidney disease in China. Emerging evidences have revealed its ability to attenuate diabetic nephropathy (DN). Tripterygium wilfordii polyglycosides (TWPs), triptolide (TP), and celastrol are predominantly active compounds isolated from TWHF. The effects and molecular mechanisms of TWHF and its active compounds have been investigated in recent years. Currently, it is becoming clearer that the effects of TWHF and its active compounds involve in anti-inflammation, anti-oxidative stress, anti-fibrosis, regulating autophagy, apoptosis, and protecting podocytes effect. This review presents an overview of the current findings related to the effects and mechanisms of TWHF and its active compounds in therapies of DN, thus providing a systematic understanding of the mechanisms and therapeutic targets by which TWHF and its active compounds affect cells and tissues in vitro and in vivo.